2014
DOI: 10.1007/s13361-014-0973-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Adnectin Binding on the Extracellular Domain of Epidermal Growth Factor Receptor

Abstract: The precise and unambiguous elucidation and characterization of interactions between a high affinity recognition entity and its cognate protein provides important insights for the design and development of drugs with optimized properties and efficacy. In oncology, one important target protein has been shown to be the epidermal growth factor receptor (EGFR) through the development of therapeutic anticancer antibodies that are selective inhibitors of EGFR activity. More recently, smaller protein derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
3
11
0
1
Order By: Relevance
“…For each peptide, the relative deuterium uptake was plotted without back-exchange correction. The average back-exchange was observed to be 24% using a highly deuterated 9-peptide standard, similar to previous data (63)(64)(65). Entire labeled samples were duplicated, and undeuterated controls were acquired in triplicate.…”
Section: Hydrogen-deuterium Exchange Mass Spectrometrysupporting
confidence: 83%
“…For each peptide, the relative deuterium uptake was plotted without back-exchange correction. The average back-exchange was observed to be 24% using a highly deuterated 9-peptide standard, similar to previous data (63)(64)(65). Entire labeled samples were duplicated, and undeuterated controls were acquired in triplicate.…”
Section: Hydrogen-deuterium Exchange Mass Spectrometrysupporting
confidence: 83%
“…This is clearly illustrated in a study that defined the binding of factor H binding protein (fHbp), a key virulence factor and vaccine antigen of Neisseria meningitides, with its bactericidal mAb 12C1 (51) as the MS and crystallography data delineated roles for both N-terminal and C-terminal peptide regions. Both HDX-MS and HRF-MS were used to map the epitope of human epidermal growth factor receptor (EPGR) that binds to adnectin, a targeted biologic derived from the fibronectin domain, these solution data were consistent with that from crystallography (52,53).…”
Section: Fig 2 Flow Chart Of Hdx-ms (Top) and Hrf-ms (Bottom)mentioning
confidence: 76%
“… 274 Seger et al engineered new disulfide bonds in human growth hormone and used HDX-ETD to investigate conformational and functional consequences of new bond positions, showing how a different disulfide bond could stabilize the protein. 275 HDX-ETD has also played a valuable role in determination of site-specific changes in enzyme activities (like coagulation factors) upon cofactor binding, 276 structural changes upon binding of epidermal growth factor receptor inhibitors in cancer treatments, 277 and oligomerization of apolipoprotein E, which can be a risk factor in Alzheimer’s disease. 278 In an interesting study, Borchers and co-workers showed how specific phosphorylation events can affect protein structure using top-down HDX-ETD experiments, providing an avenue to study how PTMs affect protein activity and binding via structural changes.…”
Section: Structural Characterization Using Etdmentioning
confidence: 99%